EFEKTIVITAS JUS PISANG DAN AIR KELAPA MUDA TERHADAP TENSI LANSIA PENDERITA HIPERTENSI - TRIPENI, TRIPENI; DIANA, SULIS (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Banana and coconut water contains high levels of potassium which can help lower bloodpressure by binding sodium in the blood to be removed through the urine. This study aims toprove the effect of the combination of banana and coconut juice on blood pressure in Panti Wreda Mojopahit Mojokerto. Researchers use quasy research design. The sample ishypertensive patients as many as 20 people were selected using purpoosive sampling, which are divided into 2 groups of 10 people were given the combination juice of young coconutwater and bananas and 10 people as control were treated for 5 days. Data tension every 30minutes after treatment were collected and analyzed using the Friedman test and the MannWhitney test. The study concluded that there are differences in systolic and diastolic bloodpressure before and after the given combination juice of young coconut water andbananas.The systolic blood pressure between juice and coconut water group are significantly different, but the diastolic blood pressure was not found any difference in the two groups. Therefore concluded that the combination is more effective of the juice affects the systolicthan diastolic blood pressure.Keyword: Amboneese Banana, coconut water, hypertension